2022
DOI: 10.1101/2022.11.08.515688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dysfunctional feedback processing in methamphetamine abuser; evidence from neurophysiological and computational analysis

Abstract: Methamphetamine use disorder associated with a dysfunctional neural feedback (reward and punishment) processing system and is considered a public health risk. Although several behavioral, computational, and electrocortical studies have explored feedback processing in other groups of individuals, the precise mechanisms of feedback processing dysfunction in methamphetamine use dependent (MUD) individuals remain unclear. Furthermore, our recent knowledge about the underlying feedback related connectivity patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 104 publications
(220 reference statements)
0
2
0
Order By: Relevance
“…However, the role of the delta band is understood to be broader, e.g., in motivation and the sustainment of concentration (Harmony 2013). Some studies provide evidence for attenuated theta and/or delta EROs, e.g., with problematic substance use (alcohol, nicotine, or cannabis) (Harper et al 2019), alcohol use disorder (AUD) (Kamarajan et al 2004;Jones et al 2006;Harper et al 2018) and methamphetamine use disorder (Ghaderi et al 2022). There is a general research opportunity to incorporate EROs in EM addiction research, and speci cally for tobacco smoking, the present study provides the rst cross-sectional results in the eld.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of the delta band is understood to be broader, e.g., in motivation and the sustainment of concentration (Harmony 2013). Some studies provide evidence for attenuated theta and/or delta EROs, e.g., with problematic substance use (alcohol, nicotine, or cannabis) (Harper et al 2019), alcohol use disorder (AUD) (Kamarajan et al 2004;Jones et al 2006;Harper et al 2018) and methamphetamine use disorder (Ghaderi et al 2022). There is a general research opportunity to incorporate EROs in EM addiction research, and speci cally for tobacco smoking, the present study provides the rst cross-sectional results in the eld.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a longitudinal study of iMUDs found that participants who decreased methamphetamine use over a period of six weeks showed higher levels of DE by the end of that period 15 , supporting the idea that methamphetamine use may affect exploratory behavior. In addition to lower levels of exploration, iMUDs have been shown to engage in maladaptive belief-updating, which is often operationalized in terms of altered learning rates within computational models [16][17][18][19][20][21] . This overall pattern of altered sensitivity to, and learning from, choice outcomes may help explain continued use and high relapse rates despite reduced quality of life 22 .…”
Section: Introductionmentioning
confidence: 99%